IMPLEMENTASI KURIKULUM PENDIDIKAN KARAKTER DI SEKOLAH DASAR ISLAM TERPADU (SDIT) - Khodijah Khodijah (Jurusan PGMI FTIK IAIN Metro Lampung, 2016)
The implementation of character education curriculum in Integrated Islamic Elementary School (SDIT) applied in the planning and implementation of character education are integrated in the learning and school culture that is applied by all citizens of the school. Character education begins with educators as one of the success factors of value investment figure character is an educator who can be a role model. In addition, as the executor of character education curriculum, educators also play an important role in the preparation of learning programs characterized by integrating the values of characters in each learning activity. Teachers are also required to plan learning professional character, because the planning is exactly the first step of the preparation of educators foster the values of character the young generation of the nation.